Serodiagnosis of Helicobacter pylori infection: comparison and correlation between enzyme-linked immunosorbent assay and rapid serological test results. - Chen, T S (1997)
CLOser is a new, one-step, qualitative anti-Helicobacter pylori immunoglobulin G test having the advantage of convenience and simplicity. We aimed to evaluate its diagnostic accuracy and to compare it with a quantitative enzyme-linked immunosorbent assay (ELISA) (HEL-pTEST II) in a study of 86 adult dyspeptic patients by using the results from histology and urease testing of gastric biopsies as a "gold standard." Forty-six patients were H. pylori positive. The sensitivities, specificities, and positive and negative predictive values were 95.7, 72.5, 80.0, and 93.5%, respectively, for CLOser and 93.5, 92.5, 93.5, and 92.5%, respectively, for HEL-pTEST II. The grade of the colored test bands in CLOser was correlated with antibody titers in HEL-pTEST II (r = 0.71; p < 0.001). The mean antibody titers were 13, 74, 186, and 328 U/ml for the negative, faint, thin, and thick bands, respectively, of CLOser. We concluded that the CLOser rapid serological test yielded sensitivity similar to that of the conventional ELISA. Although CLOser is not suitable for epidemiologic screening for H. pylori infection on account of lower specificity, it is particularly convenient and very easy to perform. Therefore, it may eventually become widely used in the office-based care of patients and lead to more cost-effective patient management decisions.